2007
DOI: 10.1590/s0104-11692007000500005
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle changes in descendants of parents with diabetes type 2

Abstract: CAMBIO EN LOS PATRONES DE VIDA EN DESCENDIENTES DE PROGENITORES CON DIABETES MELLITUS TIPO 2 DEL NORESTE DE MEXICO MUDANÇA EM OS PADRÕES DE VIDA EM DESCENDENTES DE PROGENITORES COM DIABETES MELLITUS TIPO 2 DO NORDESTE DO MEXICO O objetivo geral do estudo foi explorar à disposição à mudança dos padrões alimentares e atividade física nos descendentes de progenitores com diabetes mellitus tipo 2 (DMT2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Seventeen percent of participants presented overweight and 68% obesity. Moreover, it was identified that a considerable percentage of participants was not trying to decrease fat consumption in their diet, and that a considerable part made no intent on or would not try to practice some kind of exercise in the next six months (14) , which can be associated with the fact that children of parents with type 2 diabetes do not perceive their risk of developing this disease or do not perceive that they are obese.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen percent of participants presented overweight and 68% obesity. Moreover, it was identified that a considerable percentage of participants was not trying to decrease fat consumption in their diet, and that a considerable part made no intent on or would not try to practice some kind of exercise in the next six months (14) , which can be associated with the fact that children of parents with type 2 diabetes do not perceive their risk of developing this disease or do not perceive that they are obese.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Diet and lack of exercise are strongly related to the development of insulin resistance. (6,7) It has been reported that high-fat Western food and glycemic load are positively associated with fat deposits and insulin resistance. (8) On the other hand, even moderate exercise is effective for the improvement of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%